Prescriptions for choral excellence : tone, text, dynamic leadership - Emmons, Shirlee (Oxford University Press, 2006)
Presents research in voice science, and leadership and performance psychology. This volume addresses the topics relevant to choirs, and provides instruction on how to apply the concepts in day-to-day rehearsal and performance.